Analysis of the Contribution of Local Taxes and Regional Levies to Regional Original Revenue in Samarinda City - Fransiska Reza Karina Hayuning; Jiuhardi Jiuhardi; Muhammad Awaluddin (Budapest International Research and Critics University, 2022)
The purpose of this study to discuss about analysis of the contribution of local taxes and regional levies to regional original revenue in Samarinda City. This research is included in the type of descriptive research. The data used is secondary data, namely the Realization of Tax Revenue Report and Regional Original Revenue Report in Samarinda City obtained from the Audit Report of the Republic of Indonesia Representative Office for East Kalimantan Province from 2016 to 2020. The analysis model in this study is a quantitative form. The research results show that the contribution of local taxes to regional original revenue in Samarinda City for the last 5 years is in the very good category. The contribution of regional levies to regional original revenue in Samarinda City is in the very low category.